Practice patterns of vasal reconstruction in a large United States cohort. (29th August 2021) - Basourakos, Spyridon P.; Lewicki, Patrick; Punjani, Nahid; Arenas‐Gallo, Camilo; Gaffney, Christopher; Fantus, Richard J.; Al Hussein Al Awamlh, Bashir; Schlegel, Peter N.; Brannigan, Robert E.; Shoag, Jonathan E.; Halpern, Joshua A.
Abstract: We aimed to characterise diverse practice patterns for vasal reconstruction and to determine whether surgeon volume is associated with vasoepididymostomy performance at the time of reconstruction. We identified adult men who underwent vasal reconstruction from 2000 to 2020 in Premier Healthcare Database and determined patient, surgeon, cost and hospital characteristics for each procedure. We identified 3, 494 men who underwent either vasovasostomy‐alone ( N = 2, 595, 74.3%) or any‐vasoepididymostomy ( N = 899, 25.7%). The majority of providers ( N = 487, 88.1%) performed only‐vasovasostomy, 10 (1.8%) providers performed only‐vasoepididymostomy and 56 (10.1%) providers performed both. Median total hospital charge of vasoepididymostomy was significantly higher than vasovasostomy (39, 163, interquartile range [IQR]11, 854–53, 614 and 17, 201, IQR10, 904–29, 986, respectively). On multivariable regression, men who underwent procedures at nonacademic centres (OR 2.71, 95% CI 2.12–3.49) with higher volume surgeons (OR 11.60, 95% CI 8.65–16.00) were more likely to undergo vasoepididymostomy. Furthermore, men who underwent vasoepididymostomy were more likely to self‐pay (OR 2.35, 95% CI 1.83–3.04, p < .001) and more likely had procedures in the Midwest or West region (OR 2.22, 95% CI 1.66–2.96 and OR 2.11, 95% CI 1.61–2.76, respectively; p < .001). High‐volume providers have increased odds of performing vasoepididymostomy at the time of reconstruction but at a significantly higher cost. These data suggest possibly centralising reconstructive procedures among high‐volume providers.